(untitled) (Scientia Agropecuaria, 2021)
The aim of this study was to determine the effects of different amounts of crude glycerol (CGL) on dry matter intake, milk yield, milk protein yield, and milk fatty acid profile of dairy cows grazing on a Kikuyu-based pasture. Six Holstein cows were used in the first third of lactation (mean ± SD 559 ± 22.5 kg body weight, 43 ± 10 days in milk, and 26.8 ± 1.2 kg milk/day) and were randomized within a replicated 3 × 3 Latin square arrangement. Animals grazed the Kikuyu grass and were supplemented with a commercial energy-protein concentrate at 1.0 kg/4.0 kg of milk. The experimental period was 69 days. The following treatments were administered: CGL0 (control, without glycerol), CGL1 (750 g/cow/day), and CGL2 (1,500 g/cow/day). The addition of 750 and 1,500 g of CGL did not affect grass and concentrate intake (P > 0.05). However, milk yield (FCM 3.5%) increased by 14.2% in the CGL2 group compared to that obtained in the control group (CGL0) (P = 0.02). The addition of 1,500 g of CGL to the diet resulted in a 2.1% greater yield of milk protein compared to that obtained with CGL0 treatment (P = 0.01). Further, the addition of 1,500 g of CGL did not impact grass intake, milk fat concentration, or fatty acid composition (P < 0.05). Thus, the inclusion of CGL as a co-product may be a nutritional strategy to increase the productivity of dairy production systems in tropical perennials, such as Kikuyu grass.